Impact of carbon sources in airport de-icing compounds on the growth of Sphaerotilus natans - Exton, Benjamin; Hassard, Francis; Medina-Vaya, Angel; Grabowski, Robert C. (Frontiers in Microbiology, 2024)
Airport de-icing has been linked with the growth of undesirable river biofilms (URBs, formerly "sewage fungus"), a manifestation of organic pollution causing long-term ecological damage to watercourses. URBs are a polymicrobial community, with one key taxon standing out in literature: Sphaerotilus natans, a filamentous bacterium also found in sewage treatment and activated sludges. An industry often implicated in causing URBs is airport de-icing, with large biofilms often developing downstream of airport discharges in winter months. However, it is not yet clear which deicers may cause URBs and how they influence growth. Therefore, specific objectives were to (i) determine which freeze-point depressants (FPDs) can be utilised by S. natans; (ii) examine differences in the growth kinetics between FPDs; and (iii) compare pure-FPDs to commercial airport de-icers (CADs) as carbon sources, to determine impacts of additives. This study employed a turbidimetric micro-batch culture design to conduct microbial growth experiments, using S. natans and a minimal medium supplemented with airport de-icer as the carbon source. Equimolar carbon concentrations were used to compare the effects of common FPDs and CADseach containing a specific FPD. Growth was assessed via optical density (OD600) measurements, from which time-todetection, maximum rate of change, and maximum optical density were derived and kinetics inferred. S. natans was found to grow effectively on all FPDs tested, although the microbial yield was heavily dependent on the carbon concentration for all FPDs and CADs. Sodium acetate generated the quickest growth, with the lowest TTD (lag-time) for all but the lowest concentrations tested. Propylene glycol produced the greatest maxOD (total growth), whereas ethylene glycol had a higher limiting concentration for maxROC (growth rate). The mixture of compounds and additives in commercial products did not significantly impact the growth of S. natans. This research provides evidence from controlled laboratory experiments that airport de-icers support the growth of S. natans. The differences in growth kinetics observed for the FPDs and CADs could inform improved mitigation or treatment to reduce the incidence and ecological impacts of URBs.